Experimental and numerical study of heat transfer performance of a channel flow with an inverted flag. (1st September 2022) - Zhong, X.L.; Fu, S.C.; Chan, K.C.; Wang, L.Q.; Chao, Christopher Y.H.
Highlights: A thinner inverted flag starts flapping at a lower wind speed. The heat dissipation effect is strongly affected by the inverted flag motion. The flapping mode induces the highest average vorticity compared with other modes. The flapping mode induces the largest heat transfer enhancement compared with other modes. Abstract: It has been demonstrated that flexible vortex generators, e.g., flapping flag, can significantly enhance heat transfer inside a heat sink. However, their heat transfer enhancement is only effective when they exhibit flapping behaviors, which require a flow velocity higher than the heat sink working velocity, and thus restraint their application. Minimizing the critical flapping velocity of the flags without sacrificing the heat transfer performance is needed. In this work, we study the cases of inverted flags with different thicknesses in a channel flow. Three flag motion modes are identified by a high-speed camera with increasing flow velocity. In the first mode transition, i.e., the flag starts flapping, the heat dissipation has the highest enhancement. Numerical simulation reveals that compared to the other motion modes, the flapping mode has the strongest average vorticity along the channel wall, leading to the highest heat dissipation among all flag motion modes. Experimental results show that the critical velocity can be as low as 1.5 m/s, at which the heat dissipation enhancement can be as high as 100%. The findings in this work significantly benefit the application of flexible vortex generators in heat sinks, by enabling a decrease in critical velocity and a good enhancement in heat dissipation.